Theorising research with vulnerable people in Higher Education:Ethical and Methodological Challenges - Maringe, Felix; Sing, Nevensha (South African Journal of Higher Education, 2016)
Students in universities experience varying forms of vulnerability, which could have negative consequences for fulfilling their academic potential. The voices of these vulnerable students have not been adequately captured in existing research and can be best sought through qualitative research which targets the very students experiencing such vulnerabilities. This paper, framed within the conceptual theory of vulnerability, using Narrative Theory as a methodological approach, explores how students in universities, experience the phenomenon of being at risk, how they cope with it, and how their narratives of vulnerability can inform student retention and support in Higher Education Institutions. Being at risk is a multidimensional concept, which is not adequately dealt with in institutional ethics policy and practice. Preliminary findings suggest that students at risk feel marginalised form mainstream support services. Further, evidence suggests that doctoral students’ training reproduces the marginalisation of vulnerability through inadequately addressing ways of researching with vulnerable people. Key Words: vulnerable people, students at risk, student support, dropout, and retention